Requirements of Polygamy by Muhammad Shahrur and It’s Relevance to Indonesian Society - Alimuddin, Harwis; Abbas, Abdul Haris; Amir, Indriyani; Syatar, Abdul (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2024)
Muhammad Shahrur has a different view about polygamy from other scholars. According to him, polygamy is only permitted for widows who have orphans. This condition applies to second, third and fourth wives. This requirement refers to the principle of protection for widows and the principle of justice towards orphans. This research is descriptive qualitative research. The data collection technique is a literature study by exploring various literature, both literature in the form of books and articles related to Muhammad Shahrur's thoughts. Likewise, it is related to the social conditions of Indonesian society, especially the phenomenon of polygamy in Indonesia. This research explores Muhahmmad Shahrur's opinion regarding the requirements for polygamy and looks at its relevance to social conditions in society. This research concludes that the conditions for polygamy expressed by Muhammad Shahrur are very relevant and can bring benefits if implemented and legislated into regulations in Indonesia. First, because polygamy regulations in Indonesia adhere to the principle of open monogamy. Second, polygamy can be a solution for widows and their orphaned children in Indonesia who face many problems. Third, polygamy is not prescribed to cause problems, but to provide solutions. Including solutions to social conditions in society.